Pengembangan Kurikulum Pendidikan Agama Islam Sebagai Upaya Memperkuat Nilai-Nilai Keagamaan Berdasarkan Kearifan Lokal di Kab. Kaur Bengkulu - Siratjudin, Siratjudin; Eka Citra Dewi, Desy (Yayasan Darussalam Bengkulu, 2024)
The curriculum is one of the important tools in education. The curriculum has a central position in realizing the goals and objectives of education. The curriculum itself is a set of plans and arrangements regarding the objectives, content and learning materials, to achieve certain educational goals. The Islamic education curriculum must begin with the preparation or formulation of educational goals according to Islam. The goal of education according to Islam is the realization of a kaffah Muslim, namely a Muslim who (1) is physically healthy and strong; (2) his mind is smart and clever: (3) his heart is filled with faith in Allah. The development of these aspects must be balanced. The development of the Islamic Religious Education (PAI) curriculum has undergone a paradigm shift, although some of the previous paradigms have been maintained to date. Values in Islam contain two categories of meaning seen from a normative perspective, namely considerations of good and bad, right and wrong, haq and batil, blessed and cursed by Allah SWT. This research can provide concrete recommendations for improving the Islamic education curriculum, so that students can have a deeper understanding of Islamic teachings and be able to practice religious values in everyday life.